Dinamika Legislasi dan Reformasi Hukum di Indonesia Tahun 2025: Studi Implementasi UU No. 4 Tahun 2023 (UU PPSK) dan Dampaknya - Ikbal, Ikbal; Abi, Kemal; Alif, Sayyid; ⁠Jueni, ⁠Jueni; Endarto, Dwi Wahyu; Candra, Firman Adi (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This research comprehensively examines the dynamics of legislation and legal reform in Indonesia in 2025, with a primary focus on the implementation of Law No. 4 of 2023 concerning Financial Sector Development and Strengthening (PPSK Law). The background of this study is the urgency of strengthening financial sector regulations to maintain system stability, protect consumers, and support sustainable economic growth amidst global and domestic challenges. The main objectives are to analyze the substance of the PPSK Law, evaluate its implementation process up to 2025, identify challenges encountered, and measure its impact on the Indonesian financial sector. Employing a normative legal research method enriched with an empirical approach through document analysis and literature review, this study finds that the PPSK Law has brought significant changes in the governance and supervision of the financial sector. Nevertheless, its implementation faces various challenges, including the harmonization of derivative regulations, infrastructure readiness, and business actors' adaptation. Notable impacts include improved stability, consumer protection, and market efficiency, though continuous evaluation is needed to ensure optimal achievement of reform objectives. The research concludes by emphasizing the importance of synergy among institutions and regulatory adaptation to technological innovation.